Wavelength-tunable infrared metasurfaces with chiral bound states in the continuum - Tao Zhang; Jiachen Liu; Liangliang Gu; Haifeng Hu; Qiwen Zhan (Scientific Reports)
Abstract In recent years, research on chiral bound states in the continuum (BIC) has surged, leading to the development of various chiral metasurfaces with narrow bandwidths by breaking of in-plane and out-of-plane symmetries. However, the ability to dynamically tune the working band remains relatively unexplored, which is valuable for chiral sensing applications. Optical phase-change materials, with tunable dielectric constants and switchable properties during phase transition, offer the potential for dynamic control of optical metasurfaces. This work demonstrates a wavelength-tunable infrared chiral metasurface by combining the phase-change material GST with chiral BIC structures. By varying the longitudinal tilt angle of the nanostructure, an infrared chiral metasurface with an extremely narrow bandwidth of chiral resonance and a CD value of over 0.8 is designed. The phase-change properties of GST enable wavelength-tunable chiral resonance without altering the structural parameters, and the influence of key structural parameters of the metasurface on the chiral resonance wavelength and CD value is analyzed. The proposed chiral BIC metasurface with phase-change materials shows promising application prospects in filter devices, chiral thermal switches, infrared imaging, and tunable chiral photonics.